2019
DOI: 10.3389/fvets.2019.00369
|View full text |Cite
|
Sign up to set email alerts
|

Animal Pesticide Poisoning in Tunisia

Abstract: During the period from 2014 to 2017, a retrospective study on pesticide poisoning in domestic animals and livestock was compiled and then analyzed. A total of 71 pesticide analyses have been submitted to the Pharmacy and Toxicology Laboratory of the School of Veterinary Medicine of Sidi Thabet in Tunisia. All the cases were first referred either through the clinical and/or pathological departments of the Veterinary School, the private and/or governmental veterinarians or directly by the pet owners. Among the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…In this way, several cases of human accidental [18] , [21] , [55] , [64] , [71] or suicidal [12] , [19] , [2] , [51] , [57] , [64] poisoning by DZN have been reported, some of which were fatal. Also, cases of fatal intoxication in animals are reported [10] , [13] , [26] , [36] , [40] , [61] . The dose of DZN observed to cause a cytotoxic effect in the present study (25–150 μM) is in line with the human blood concentration of 28 mg/dL (0.91 mM) achieved following acute self-poisoning [51] .…”
Section: Discussionmentioning
confidence: 99%
“…In this way, several cases of human accidental [18] , [21] , [55] , [64] , [71] or suicidal [12] , [19] , [2] , [51] , [57] , [64] poisoning by DZN have been reported, some of which were fatal. Also, cases of fatal intoxication in animals are reported [10] , [13] , [26] , [36] , [40] , [61] . The dose of DZN observed to cause a cytotoxic effect in the present study (25–150 μM) is in line with the human blood concentration of 28 mg/dL (0.91 mM) achieved following acute self-poisoning [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently used substances in poisonous baits were strychnine, carbamate, and organophosphorus compounds (Parvanov et al 2018). Moreover, highly toxic pesticides were detected in intentional poisoning of domestic animals and wildlife in Spain (aldicarb, carbofuran and strychnine) (Martínez-Haro et al 2008), Italy (insecticides -anticholinesterases, rodenticides, molluscicides and herbicides) (Chiaria et al 2017), Tunisia (carbamates, organophosphates and rodenticides-anticoagulants) (Lahmar et al 2019) and Hungary (carbofuran, brodifacoum, terbufos and diazinon) (Deák et al 2020a). In correspondence with these findings, our results showed that laboratory confirmed intoxications in EIEs from the study were caused by anticholinesterase's inhibitors such as organophosphate and carbamate insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca zehirleyici maddeler sıklık açısından sırasıyla antikoagülan rodentisitler, organik fosforlu insektisitler, antikoagülan olmayan rodentisitler, molluskusit ve herbisitler, diğer zehirleyici bileşikler olarak tespit edilmiştir. Ölümle sonuçlanan pestisit zehirlenme vakalarında, karbamatlı pestisitlerin öne çıktığı, bunun yanı sıra organik fosforlu pestisitler, rodentisitler, mikotoksinler gibi zehirleyici ajanların da sıkça ölüme sebep olduğu belirtilmektedir (29,41). Allkämper ve ark.…”
Section: Tartışma Ve Sonuçunclassified
“…Tür bazında zehirlenme şüpheli vaka sayısı çoktan aza doğru köpek, sığır, koyun, kanatlı hayvanlar, kedi, egzotik hayvanlar, keçi, manda ve at sırasıyla tespit edilmiştir. Dünya genelinde yapılan retrospektif çalışmalarda da hayvan zehirlenmelerine en sık maruz kalan tür köpekler olarak ortaya çıkmaktadır (2,6,13,15,29). Amerika Birleşik Devletleri ve Kanada'da 2002-2010 yılları arasında tespit edilen zehirlenme şüpheli vakalarının % 76'sı köpeklerde, % 13'ü kedilerde gerçekleşmiştir (31).…”
Section: Tartışma Ve Sonuçunclassified